Preparation of H3PO4 modified Sidr biochar for the enhanced removal of ciprofloxacin from water. Issue 12 (15th October 2022) - Iqbal, Jibran; Mohamed Al Hajeri, Buthaina; Shah, Noor S.; Wilson, Kenesha; Xavier, Cijo; Shaalan, Jwaher; Al-Taani, Ahmed A.; Howari, Fares; Nazzal, Yousef
Abstract: In this study, biochar was prepared from Sidr plant leaves and used for the treatment of ciprofloxacin (CIP)-contaminated water. CIP is important class of emerging water pollutants from pharmaceutical industries. The biochar showed 65% adsorption efficiency and 43.48 mg/g adsorption capacity of CIP. Adsorption efficiency as well as adsorption capacity were improved to 91% and 62.50 mg/g, respectively, by phosphoric acid (H3 PO4 ) modified biochar. Removal of CIP by the prepared biochar was due to different surface functional groups of CIP and biochar as revealed from the study of different characterization analyses. The presence of PO4 3– group in modified biochar led to maximum binding of CIP. Also, the modified biochar showed higher reusability potential and less leaching of ions when compared to the raw biochar. Removal of CIP was affected by concentrations of CIP, the amount of biochar and different pH's; the maximum removal of CIP was achieved at pH 4. The Freundlich and pseudo-first-order models best fitted the removal of CIP by modified biochar. Advanced characterization techniques were applied to investigate surface and physiological characteristics of the biochar and modified biochar. The modification showed high impact on the performance and stability of biochar. The study showed significant impacts of modification on the potential of the biochar for treatment of CIP-contaminated water. Graphical abstract: UF0001